Does ENSO Significantly Affect Rice Production In Indonesia? A Preliminary Study Using Computational Time-Series Approach - Herho, Sandy H. S.; Brahmana, Ferio; Herho, Katarina E. P.; Irawan, Dasapta E. (International Journal of Data Science, 2021)
ENSO is a phenomenon that is suspected to inﬂuence rice production in Indonesia. In this study, we try to ﬁnd direct correlation between ENSO and rice production in this region by using various latest computational time series methods, such as Dynamic Time Warping, Wavelet Coherence, and Bayesian Structural Time Series to quantify the statistical relationship between the Multivariate ENSO Index on annual rice production in 1961- 2019. We did not ﬁnd a direct correlation between these two variables, which may be due to the local inﬂuence of ENSO on different rice production areas in Indonesia. This study would also point out the importance of shifting the theme of research in Indonesia from mapping to monitoring and freely share the data. This step would bring science to progress further and faster.